The Oncogene Transcription Factor EB Regulates Vascular Functions - Doronzo, Gabriella; Astanina, Elena; Bussolino, Federico (Frontiers in Physiology, 2021)
Transcription factor EB (TFEB) represents an emerging player in vascular biology. It belongs to the bHLH-leucine zipper transcription factor microphthalmia family, which includes microphthalmia-associated transcription factor, transcription factor E3 and transcription factor EC, known to be deregulated in cancer. The canonical transcriptional pathway orchestrated by TFEB adapts cells to stress in all kinds of tissues by supporting lysosomal and autophagosome biogenesis. However, emerging findings highlight that TFEB activates other genetic programs involved in cell proliferation, metabolism, inflammation and immunity. Here, we review the activities of TFEB in vascular system in embryo and in adult life. Recognizing vascular TFEB as a hub of a network of signals between tissues and bloodstream provides a fresh perspective on the molecular principles regulating organogenesis and tissue functions in physiology and pathology, promising to unveil new vulnerabilities characterizing chronic and degenerative diseases.